Performance study of modified Pt catalysts for the complete oxidation of acetone. (12th October 2019) - Ge, Yunli; Fu, Kaixuan; Zhao, Qian; Ji, Na; Song, Chunfeng; Ma, Degang; Liu, Qingling
Graphical abstract: A series modified Pt catalyst with excellent acetone catalytic oxidation activity and CO2 selectivity through a relatively low temperature range. Highlights: Modified Pt catalyst was prepared for LTCO of acetone. Excellent catalytic activity and CO2 selectivity at a low temperature range. The addition of Ce can promote the formation of more Pt 0 (metal) on the support. Abstract: Low temperature catalytic oxidation (LTCO) is an effective method of treatment for low concentrations of volatile organic compounds (VOCs) that uses efficient catalysts to reduce reaction activation energy and to improve reaction rates. A series of modified Pt catalysts (Pt-Ce, Pt-Zr) were successfully prepared, and they were used as catalysts for acetone oxidation. Several methods such as X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), transmission electron microscopy (TEM) and Hydrogen-temperature-programmed reduction (H2 -TPR) have been used to explore the reaction mechanisms between catalysts and acetone. The results show that Ce-modified Pt catalysts (Pt-Ce/TiO2 ) display excellent performance for acetone oxidation, and the T50 (temperature at 50% conversion rate) and T90 of Pt-Ce/TiO2 are 210 °C and 236 °C, respectively. The XPS results show that the amount of Pt 0 (metal) in the Pt-Ce/TiO2 was significantly higher than that in the Pt/TiO2 . The addition of Ce favors the formation of more Pt 0 (metal) on the catalyst surface, which accelerates the acetone oxidation. It can be concluded that the additional Pt nanoparticles exposed to the catalyst surface accelerated the process of acetone oxidation.